If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(3p + 3) + -2(6 + -11p) = 3(6 + 4p) Reorder the terms: -3(3 + 3p) + -2(6 + -11p) = 3(6 + 4p) (3 * -3 + 3p * -3) + -2(6 + -11p) = 3(6 + 4p) (-9 + -9p) + -2(6 + -11p) = 3(6 + 4p) -9 + -9p + (6 * -2 + -11p * -2) = 3(6 + 4p) -9 + -9p + (-12 + 22p) = 3(6 + 4p) Reorder the terms: -9 + -12 + -9p + 22p = 3(6 + 4p) Combine like terms: -9 + -12 = -21 -21 + -9p + 22p = 3(6 + 4p) Combine like terms: -9p + 22p = 13p -21 + 13p = 3(6 + 4p) -21 + 13p = (6 * 3 + 4p * 3) -21 + 13p = (18 + 12p) Solving -21 + 13p = 18 + 12p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-12p' to each side of the equation. -21 + 13p + -12p = 18 + 12p + -12p Combine like terms: 13p + -12p = 1p -21 + 1p = 18 + 12p + -12p Combine like terms: 12p + -12p = 0 -21 + 1p = 18 + 0 -21 + 1p = 18 Add '21' to each side of the equation. -21 + 21 + 1p = 18 + 21 Combine like terms: -21 + 21 = 0 0 + 1p = 18 + 21 1p = 18 + 21 Combine like terms: 18 + 21 = 39 1p = 39 Divide each side by '1'. p = 39 Simplifying p = 39
| 3(w-1)=2w | | X^7=9 | | 7y+5+y=43 | | -4(x-4)=(2-1) | | f(x)=-2-1 | | k^2=14k-48 | | 11=7+(1-x) | | 3x-4=10x+7 | | 7x-(5x+5)=3x-47 | | 20+5x-4x=-6x+2 | | 4x+6x+3+9=5x+5+4x | | 4-2x=8-5x+5 | | (6x-1)(5x+4)=0 | | (6y+7)-(3+5y)=8 | | Y=x^24-3x^12-88 | | a^2=-10+7a | | (6x-1)(5x+4)=0 | | (4y+4)-(2+3y)=12 | | -2.5x+4=-1 | | 7-2x=1-3x | | 10=0.2y | | v^2+6v=-9 | | (8x-8)=(7x-2x) | | 37=5m+4 | | 11x-8y=12 | | n^2+-18n=40 | | 14=9n+12 | | x^2+8x-5=9x+1 | | x^5-4x^4+30x^3-102x^2+125x-50=0 | | 7*15=g | | x^2+12x+9=7x+3 | | c+32=44 |